Sibley, Cloud County - Woellhof, Kaitlin (Kansas State University, The Chapman Center for Rural Studies, 2011)
Sibley Township, primarily settled by homesteaders from Sweden, Norway, and England, was formally organized in 1866. However, the first settlements in the area date back to 1860 at Lake Sibley. Sibley has a rich history, but ultimately lost out to the favored town of Concordia in Cloud County
Kaitlin Woellhof, “Sibley, Cloud County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/57.
Keywords: Cloud County; Sibley; Pawnee; Concordia Blade Empire; Cheyenne; Adell and Hannie Poore